2021
DOI: 10.1177/10422587211043354
|View full text |Cite
|
Sign up to set email alerts
|

Is There Opportunity Without Stakeholders? A Stakeholder Theory Critique and Development of Opportunity-Actualization

Abstract: How can stakeholder theory contribute to opportunity theory? We suggest that stakeholder theory affords appropriate theoretical lenses for grounding the opportunity-actualization perspective more firmly within the real-world constraints of business venturing. Actualization departs from a strong focus on entrepreneurial agency to conceptualize how pre-existing environmental conditions determine what entrepreneurial action can achieve. We explain that stakeholder theory can strengthen the outward-looking orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 164 publications
(279 reference statements)
1
30
0
Order By: Relevance
“…Unlike academic fields throughout management and the social sciences, entrepreneurship literature rarely makes power a focal lens. Studies that have investigated power more explicitly (e.g., Baker & Welter, 2020;Ramoglou et al, 2021) tend not to embrace the multifaceted nature of the concept. Building on Foucault (1978), who argued that power can come from everywhere, we have re-examined the extant entrepreneurship literature to detect and illustrate how different forms of power shape opportunities and the judgment about them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike academic fields throughout management and the social sciences, entrepreneurship literature rarely makes power a focal lens. Studies that have investigated power more explicitly (e.g., Baker & Welter, 2020;Ramoglou et al, 2021) tend not to embrace the multifaceted nature of the concept. Building on Foucault (1978), who argued that power can come from everywhere, we have re-examined the extant entrepreneurship literature to detect and illustrate how different forms of power shape opportunities and the judgment about them.…”
Section: Discussionmentioning
confidence: 99%
“…The power to perspective better explains why and how entrepreneurial firms have defied existing power structures. While entrepreneurs are often seen as powerless actors, they still have the power to mobilize and influence other stakeholders to realize their opportunities (Ramoglou et al, 2021). By activating power resources, in particular noncoercive forms such as authority that often grant them soft power (Nye, 2011;Santos & Eisenhardt, 2009), entrepreneurs may evade, counteract, or challenge existing power structures and be a productive source of welfare gain.…”
Section: Discussionmentioning
confidence: 99%
“…We found that successful entrepreneurship is both actor- and context-dependent (Welter, 2011). Thus our study helps reinstate the conceptual balance between “the agent” and the agency of the entrepreneur (Alvarez and Barney, 2007; Sarasvathy, 2001) and “the environment” by underscoring the contingencies (Davidsson, 2020; Ramoglou et al , 2021) necessary for the realization of entrepreneurial aspirations (Johns, 2017; Ramoglou and Tsang, 2016; Welter, 2011). Our empirical insights add nuance to the recent turn toward the complex interplay of the environmental conditions facilitating the actualization of desirable futures (Davidsson et al , 2020; Dimov, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…Entrepreneurship can be defined as the scholarly examination of how enterprise ideas are institutionalized by entrepreneurial actors through relational process to generate social and economic value (Karataş-Özkan and Chell, 2010). The role of actors, in particular the entrepreneurs, is critical in leading change and generate enterprise (Battilana et al , 2009), but contemporary entrepreneurship literature emphasizes the centrality of contingencies that condition entrepreneurial success (Davidsson, 2020; Ramoglou et al , 2021), representing a shift from the traditional focus on entrepreneurship’s agents (Alvarez and Barney, 2007; Sarasvathy, 2001).…”
Section: Entrepreneurial Careers In Restaurant Businessmentioning
confidence: 99%
“…Their process model details how moral imagination enhances moral legitimacy and stakeholder support by broadening stakeholder awareness and engagement, empathizing with secondary stakeholders and creating microsocial norms. Ramoglou et al (2022), in their article titled "Is There Opportunity Without Stakeholders? A Stakeholder Theory Critique and Development of Opportunity-Actualization," clarify the opportunity space by developing a logic that narrows and deepens the construct, using stakeholder theory to strengthen the outward-looking orientation of other opportunity theories.…”
mentioning
confidence: 99%